Materials for interconnection structures. Sectional specification set for reinforced base materials, clad and unclad. Epoxide cross-plied linear fibreglass-reinforced laminated sheets of defined flammability (vertical burning test) copper clad Part 2-19, (2nd May 2002) - British Standards Institution,
No abstract available